Academic Quality Assurance Model in Enhancing The Competitive Advantage of Nahdlatul Ulama University - Siti Nur Afifah; Abd. Haris; M. Fahim Tharaba (Islamic Education Management Study Program, Faculty of Tarbiyah, Sunan Drajat Islamic Boarding School Institute, Lamongan, East Java, Indonesia., 2026)
Academic quality assurance has become a strategic necessity amid global competition, digital transformation, and the Sustainable Development Goals, yet universities affiliated with Nahdlatul Ulama (PTNU) face the added challenge of reconciling national academic standards with the preservation of Ahlussunnah wal Jama’ah institutional identity. This study analyzes and develops an academic quality assurance model for strengthening the competitive advantage of PTNU institutions. Employing a qualitative multisite case study at Universitas Islam Malang and Universitas Nahdlatul Ulama Surabaya, data were collected through in-depth interviews, participant observation, and document analysis with university leaders, quality assurance units, lecturers, and institutional stakeholders, and analyzed using interactive data condensation, display, and cross-site comparison. Both institutions implement quality assurance through integrated policies, continuous evaluation, digital governance, and the internalization of Aswaja An-Nahdliyah values into academic culture. Unlike conventional Total Quality Management models that treat institutional culture as peripheral context, this study’s central novelty is demonstrating that Islamic ideological identity functions as an active, difficult-to-replicate governance resource that directly shapes policy formulation and translates into measurable institutional gains, including superior accreditation, stronger stakeholder trust, and international recognition. The study contributes a contextual, value-based academic quality assurance model for Islamic higher education and offers strategic guidance for university leaders and policymakers seeking to align academic governance with institutional identity in faith-based universities.